2016
DOI: 10.1186/s40623-016-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of damaged urban areas using interferometric SAR coherence change with PALSAR-2

Abstract: The interferometric SAR coherence-change technique with coherence filter and polarization (HH and HV) has been used to detect the parts of buildings damaged by the 2015 Gorkha Earthquake. A survey of the building damage was conducted in every house to evaluate the detection accuracy in the Khokana and Sankhu urban areas in the Kathmandu Valley of Nepal. The damaged parts of the urban area were adequately detected using coherence-change (∆γ) values obtained before the earthquake (γ pre ) and during the inter-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 15 publications
1
34
0
1
Order By: Relevance
“…This study thus demonstrates that it is feasible to combine and extend the advantages of two different remote sensing sensors for earthquake damage assessments. The urban damage levels following the 2016 Kumamoto earthquake were obtained from the degree of interferometric coherence of pre-seismic and co-seismic data, and the findings were consistent with the results of previous research reports that mapped the urban damage [11][12][13]15] and liquefaction areas [27] by using interferometric coherence.…”
Section: Overall Studysupporting
confidence: 87%
See 2 more Smart Citations
“…This study thus demonstrates that it is feasible to combine and extend the advantages of two different remote sensing sensors for earthquake damage assessments. The urban damage levels following the 2016 Kumamoto earthquake were obtained from the degree of interferometric coherence of pre-seismic and co-seismic data, and the findings were consistent with the results of previous research reports that mapped the urban damage [11][12][13]15] and liquefaction areas [27] by using interferometric coherence.…”
Section: Overall Studysupporting
confidence: 87%
“…We evaluated buildings damaged by the earthquake [10][11][12] and detected areas of soil liquefaction [27]. The normalized difference (ND) of the coherence change (Equation (2)) was also used to detect damaged areas [9,13]:…”
Section: Interferometric Sar Coherence Change For the Earthquake Damamentioning
confidence: 99%
See 1 more Smart Citation
“…Then, three main components were quantitatively considered in the discriminant analysis: first, the revised absolute mean differential coherence (|c r |); secondly, the absolute mean differential intensity ( d ); and thirdly, the binary map derived from optical imagery. Because the main SAR scattering mechanism over the built-up areas is double-bounce scattering, the incorporation of SAR intensity and SAR coherence for VV and HH polarizations resulted in higher values at an orientation angle (ϕ) near 0 • ; moreover, the incorporation of SAR intensity and SAR coherence for VH and HV polarizations also resulted in higher values with ϕ ≥ 0 • [31][32][33]. By incorporating different polarizations, the effect of ϕ as an important parameter on both the building orientation and the power signature is taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Aerospace Exploration Agency (JAXA) operates ALOS-2 to observe various disasters. Analytical results in the 2015 Nepal Gorkha Earthquake using ALOS-2 with the 10-m resolution mode suggested that a single building can be detected by interferometric analysis [21,22]. However, the 10-m resolution was too rough compared with the scale of the building.…”
Section: Introductionmentioning
confidence: 99%